1993
DOI: 10.7567/jjaps.32s3.128
|View full text |Cite
|
Sign up to set email alerts
|

Study of Se–Te–Sb System for Application to Reversible Optical Data Storage

Abstract: In the present work variation of the two main parameters–viscosity and critical cooling rate, required for the recent upcoming optical data storage devices, have been analysed for different compositions of Se80-x Sb x Te20 (0≤x≤9) system. Temperature dependence of viscosity has been determined using the activation energy for glass transition and for crystallization obtained from heating rate dependence of glass transition temperature and peak crystalliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…To improve its properties, certain additives are used. Glassy alloys of the Se-Te system have become materials of considerable commercial importance and are widely used for optical recording media because of their excellent laser writing sensitivity in xerography, and electrographic applications such as photoreceptors in photocopying and laser printing [5] but these advantages depend on material stability [6]. Experimental results reported by various workers have shown that the addition of impurity atoms in binary Se-Te systems changes the optical properties of chalcogenide glassy semiconductors.…”
Section: Introductionmentioning
confidence: 98%
“…To improve its properties, certain additives are used. Glassy alloys of the Se-Te system have become materials of considerable commercial importance and are widely used for optical recording media because of their excellent laser writing sensitivity in xerography, and electrographic applications such as photoreceptors in photocopying and laser printing [5] but these advantages depend on material stability [6]. Experimental results reported by various workers have shown that the addition of impurity atoms in binary Se-Te systems changes the optical properties of chalcogenide glassy semiconductors.…”
Section: Introductionmentioning
confidence: 98%
“…2,3 There are promising applications in the field of laser surgery and radiometric low-temperature measurement. 5 Glassy alloys of the Se -Te system based on selenium have become materials of considerable commercial importance and are widely used for optical recording media because of their excellent laser writer sensitivity, 6 but these advantages depend on material stability. 4 Sulfide glasses exhibit an excellent 3-5 mm spectral band due to overtone absorptions of the fundamental cation-sulfur bonds such as Ge-S (As-S) which cut off the transmission between 10 and 11 mm in the 1 mm thick glass sample.…”
Section: Introductionmentioning
confidence: 99%
“…Chalcogenide glassy alloys based on amorphous Se have found various applications in different fields, such as: optical recording media because of their excellent laser writer sensitivity [12,13], infrared spectroscopy [14], transistors, detectors [15,16], rectifiers, photocells, switching, memories [17], xerography, and electrographic applications such as photoreceptors in photocopying, laser printing [18], and laser fiber techniques [19][20][21][22]. In the pure state Se has disadvantages because of its short lifetime and low sensitivity [23].…”
Section: Introductionmentioning
confidence: 99%